2015
DOI: 10.1371/journal.pone.0133686
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of and Conservation Strategies for Wild Pyrus ussuriensis Maxim. in China

Abstract: Pyrus ussriensis Maxim. is native to the northern part of China, but whose habitats are currently being destroyed by environmental changes and human deforestation. An investigation of population structure and genetic diversity of wild Ussurian pear is a priority in order to acquire fundamental knowledge for conservation. A total of 153 individuals of wild Ussurian pear from the main habitats, Heilongjiang, Jilin, and Inner Mongolia in China, possessed low genetic diversity as a result of habitat fragmentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 52 publications
4
26
0
1
Order By: Relevance
“…Genetic diversity is an important component of biodiversity, and is the basis of ecosystem and species diversity [1][2][3]. Understanding the genetic diversity and structure of germplasm resources aids efficient and rational development, and the utilization of germplasm resources on the premise of effective protection [4][5][6][7]. The growth characteristics of trees involve reaching a large size with a long growth cycle; therefore, it is necessary to analyze their genetic diversity and population structure.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity is an important component of biodiversity, and is the basis of ecosystem and species diversity [1][2][3]. Understanding the genetic diversity and structure of germplasm resources aids efficient and rational development, and the utilization of germplasm resources on the premise of effective protection [4][5][6][7]. The growth characteristics of trees involve reaching a large size with a long growth cycle; therefore, it is necessary to analyze their genetic diversity and population structure.…”
Section: Introductionmentioning
confidence: 99%
“…CONSERVATION IMPLICATIONS. Continuous urbanization and climate change have led to a decreased number of populations of wild pear species in China over recent decades, and genetic diversity of those wild pears has gradually eroded (Liu et al, 2012;Wuyun et al, 2013Wuyun et al, , 2015. Measures including ex situ and/or in situ conservation approaches should be performed to preserve the germplasm of wild Pyrus species.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the genetic diversity of a few Pyrus species has been evaluated by noncoding regions of cpDNA; Liu et al (2013) and Wuyun et al (2013Wuyun et al ( , 2015 used different cpDNA fragments to evaluate the genetic diversity of P. pashia and P. ussuriensis, respectively. Our previous study using cpDNA showed that P. betulaefolia populations in northern China contained a high level of genetic diversity and experienced rapid range expansion (Zong et al, 2014), and both restricted gene flow with isolation by distance (IBD) and allopatric fragmentation were crucial processes responsible for shaping the genetic patterns of P. betulaefolia.…”
mentioning
confidence: 99%
“…Para fines de mejoramiento genético los análisis de estructuración poblacional son fundamentales (Wuyun et al, 2015). Los clados obtenidos con estos análisis permiten agrupar diferentes poblaciones de la misma especie en grupos estructurados biológicamente.…”
Section: Perspectivas De Estudios Genéticos De Vertebrados En Loretounclassified